Pathogenicity and genomic changes of a 2016 European H5N8 highly pathogenic avian influenza virus (clade 2.3.4.4) in experimentally infected mallards and chickens - Leyson, Christina; Youk, Sung-su; Smith, Diane; Dimitrov, Kiril; Lee, Dong-Hun; Larsen, Lars Erik; Swayne, David E.; Pantin-Jackwood, Mary J. (Virology (New York, N.Y.), 2019)
Highly pathogenic avian influenza H5N8 clade 2.3.4.4 virus caused outbreaks in poultry and unusually high mortality in wild birds in 2016–2017. The pathobiology of one of these viruses was examined in mallards and chickens. High mortality and transmission to direct contacts were observed in mallards inoculated with medium and high doses of the virus. However, in chickens, high mortality occurred only when birds are given the high virus dose and no transmission was observed, indicating that the virus was better adapted to mallards. In comparison with the virus inoculum, viral sequences obtained from the chickens had a higher number of nucleotide changes but lower intra-host genomic diversity than viral sequences obtained from the mallards. These observations are consistent with population bottlenecks occurring when viruses infect and replicate in a host that it is not well adapted to. Whether these observations apply to influenza viruses in general remains to be determined.